Role of hematological parameters in the early detection of clinical cases for septicemia among neonates: A hospital-based study from Chennai, India - Jeivanth S.B.; Shreemathee Baskar; Mohammad Fareed; K. Santhosh Kumar; Osama Elshahat Mostafa; Amen Bawazir; Khalid I. AlQumaizi (PLoS ONE, 2025)
Background Neonatal sepsis, a leading cause of newborn mortality, arises from systemic infections due to an immature immune system. Its subtle early symptoms complicate timely diagnosis. Hematological parameters act as an indicator for early detection, crucial for prompt treatment, improving prognosis, and are not a challenging or cumbersome process. Aim The primary objective was to evaluate the significance of hematological parameters including red blood cell (RBC), WBC, and platelet counts in the context of neonatal sepsis. Methods This hospital-based cohort study examined 73 neonates admitted to the neonatal intensive care unit (NICU) of Saveetha Medical College and Hospital, Chennai, India during the period of January 2023 to March 2024. All the new born patients were presented with blood culture-confirmed septicemia. Results The investigation identified Klebsiella pneumoniae as the most prevalent etiological agent (26.02%), followed by Coagulase-Negative Staphylococci (CONS) and Acinetobacter baumannii (both 8.2%). Alterations in total leukocyte count and hematocrit were observed in 57% and 68.1% of cases, respectively, providing a prompt indication of infection status. Subsequent analyses revealed prominent leukocytosis, hematocrit irregularities, and thrombocytopenia, frequently manifesting in septic cases and demonstrating potential as early markers for neonatal sepsis. Conclusion The study highlights the diagnostic value of hematological alterations, such as leukocytosis and hematocrit distortion, in the prompt identification of septicemia among neonates. Based on the findings, it is recommended that routine hematological screening to be integrated as a standard component of neonatal sepsis diagnosis for rapid investigation of neonatal sepsis.